Bridging Theory and Practice: A Learning Management Model for Enhancing Entrepreneurial Creativity and Competency in Students - Ramli, Akhmad; Julaiha, Siti; Afendi, Achmad Ruslan; Anwar, Chairul; Boukhedimi, Chems Eddine (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Education plays a crucial role in shaping the mindset and practical skills students need to navigate the ever-evolving workplace. However, learning practices that focus too heavily on theory lead to suboptimal development of entrepreneurial skills. This study aims to analyze a learning management model that can strengthen students’ motivation, creativity, and entrepreneurial competency. This study employed a qualitative case study approach, collecting data through interviews, observation, and documentation. Thematic analysis was used to process the data through six phases: identifying the data, developing initial codes, identifying and reviewing themes, and producing a final report. The results indicate that hands-on experience, entrepreneurial projects, mentoring, and community collaboration play a significant role in shaping students’ business attitudes and skills. This model has been shown to enhance their independence, problem-solving abilities, and practical readiness for entrepreneurship. However, challenges such as limited facilities and the need for teacher training remain. These findings provide a theoretical contribution to the development of entrepreneurial learning management and offer an applicable model that other schools can adapt.